Novel and efficient synthesis of azaarene-substituted 3-hydroxy-2-oxindoles via sp(3) C-H functionalization of 2-methyl azaarenes and (2-azaaryl)methanes over a heterogeneous, reusable silica-supported dodecatungstophosphoric acid catalyst - Mulla, Shafeek Abdul Rashid; Pathan, Mohsinkhan Y.; Chavan, Santosh S. (RSC Advances, 2013)
A novel and efficient protocol has been developed for the synthesis of azaarene-substituted 3-hydroxy-2-oxindoles via sp(3) C-H functionalization of 2-methyl azaarenes and (2-azaaryl)methanes with isatin in good to excellent yield. This is the first example in which heterogeneous, reusable silica supported dodecatungstophosphoric acid (DTP/SiO2) catalyzed sp(3) C-H functionalization of 2-substituted azaarenes and (2-azaaryl)methanes.